SYSTEMATIC LITERATURE REVIEW : EFEKTIVITAS SISTEM INFORMASI AKUNTANSI KOPERASI DI INDONESIA (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2021)
This study aims to fill the research gap by providing a systematic literature review of the factors that influence the effectiveness of the accounting information system in cooperative in Indonesia. This research method uses a systematic literature review process which consists of three stages, namely, planning, implementation and reporting. The initial study found 316 research articles, and used a total of 10 studies for this systematic literature review based on inclusion and exclusion criteria. The extraction of selected primary research, selected and collected quantitative data will help answer a question in this research. The results of a systematic literature review of all research contained in journals published from 2015 to 2020 state that the factors that influence the effectiveness of cooperative accounting information systems in Indonesia are very diverse, namely the existence of factors of personal technical ability, user involvement, technology utilization, age, education level. , training and education programs, work experience, employee knowledge in accounting, the sophistication of information technology, individual performance, task complexity, system development formalization, manager support, company size, the presence of a steering committee, and the location of the steering department. The main factor that influences is user involvement where the cooperative should provide education and training in accounting information system programs so as to increase the user's expertise and be able to make accounting information systems effective and make decisions.Keywords: Systematic Literature Review, Effectiveness of accounting information systems, Cooperative